Konflik Yurisdiksi antara Arbitrase dan Pengadilan Niaga - sujitno sujitno (Fakultas Hukum Universitas Islam Indonesia, 2002)
This article is aimed to discuss jurisdiction conflict between arbitration and Trade Court related to the exustence of arbritration on a contract Arbritration is going to possess juridictlon ifthe case have correlation with the existence of proposal onbankruptcy accordance with the requirements managed in theActs of bankruptcy.